Directional porin binding of intrinsically disordered protein sequences promotes colicin epitope display in the bacterial periplasm - Housden, NG; Rassam, P; Lee, S; Samsudin, F; Kaminska, R; Sharp, C; Goult, JD; Francis, M-L; Khalid, S; Bayley, H; Kleanthous, C (American Chemical Society, 2018)
Protein bacteriocins are potent narrow spectrum antibiotics that exploit outer membrane porins to kill bacteria by poorly understood mechanisms. Here, we determine how colicins, bacteriocins specific for Escherichia coli, engage the trimeric porin OmpF to initiate toxin entry. The N-terminal ∼80 residues of the nuclease colicin ColE9 are intrinsically unstructured and house two OmpF binding sites (OBS1 and OBS2) that reside within the pores of OmpF and which flank an epitope that binds periplasmic TolB. Using a combination of molecular dynamics simulations, chemical trimerization, isothermal titration calorimetry, fluorescence microscopy, and single channel recording planar lipid bilayer measurements, we show that this arrangement is achieved by OBS2 binding from the extracellular face of OmpF, while the interaction of OBS1 occurs from the periplasmic face of OmpF. Our study shows how the narrow pores of oligomeric porins are exploited by colicin disordered regions for direction-specific binding, which ensures the constrained presentation of an activating signal within the bacterial periplasm.